Congenital Aortocaval Fistula from Right Subclavian Artery to Superior Vena Cava in an Adult with Tetralogy of Fallot - Soheila Chamanian; Mohammad Hassan Nezafati; Ahmad Amouzeshi; Farveh Vakilian; Toktam Moghiman (Journal of Cardio-Thoracic Medicine, 2014)
Congenital   aortocaval   fistula in association with complex congenital heart disease has never been described before. We represent an adult with tetralogy of fallot and an undiagnosed subclavian artery to superior vena cava fistula in previous catheterisms. He underwent surgical correction, successfully. After 8 months post operation he was doing well with improved functional capacity and no cyanosis.